Determinants of Female Early Marriages: A Case Study of District Lodhran, Pakistan - Gill, Abid Rashid; Abdullah, Maryam; Hassan, Nadia; Perveen, Shabana (Pakistan Journal of Humanities and Social Sciences, 2023)
Early marriage refers to child marriage before the age of 18. It is a global issue of grave concerns about teenagers' health, social well-being, and human rights. Early marriages are disproportionately more common among poor women of less developed nations. Almost half of child marriages take place in South Asia. It requires designing effective local community interventions to avoid poverty, poor health, nutrition deprivations, and other adverse consequences. While Pakistan homes about 19 million underage brides, until recently, it has not paid enough attention to evidence-based policy development. Particularly, the research on child marriages in less developed regions like South Punjab is limited. This study has explored the factors inducing early marriages from the perspective of child brides in a local community setup. Data is collected through a self-administrated and regionally representative survey from March to April 2020 using snowball sampling. Descriptive statistics, association measures, and binary logistic regression are used for analysis. The reliability and validity of the instrument are checked by confirmatory analysis. It is observed that literacy levels reduce the odds of early marriages among females. However, poverty and mass media exposure are likely to induce underage marriages of females positively. Disparities in gender and region are also significant factors for females' early marriages. For instance, the ratio of early marriages in rural areas is higher than in urban areas. In addition, the employment status and parental perception about early marriage also adversely affect child marriage. These findings suggest that the primary education of girls should be made compulsory. Policies must consider increasing and improving the media exposure and employment opportunities in South Punjab to provide support and empower vulnerable females.